De Guchteneire, P.; Pécoud, A., and Cholewinsky, R. (Eds.): Migration and Human rights. The United Nations Convention on Migrant Workers’Rights - Aravena Aguilera, Mauricio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Unesco Publishing, and Cambridge University Press, 2009, 452 pp.